Avaliação de compostos derivados de plantas brasileiras na busca de protótipos a fármacos com atividade antileishmanial - Paula Souza Lage (2015)
Leishmaniasis are diseases caused by protozoan parasites of the genus Leishmania and are endemic in about 98 countries worldwide. The pentavalent antimonials, Pentostam® (sodium stibogluconate) and Glucantime® (meglumine antimoniate), became the first-line drugs for treatment. However, its continued use causes Nephrotoxicity, Cardiotoxicity and hepatic toxicity. Alternative line drugs include pentamidine, amphotericine B (also in lipid formulations), paromomycin, and miltefosine. However, it have high toxicity and high cost and the mitelfosine is a teratogenic agent. Thus, the aim of this study was to evaluate the antileishmanial activity of some brazilian plants, in order to seek new alternatives, with lower toxicity, to use on leishmaniasis treatment. Alchornea glandulosa, Miconia latecrenata, Psychotria suterella and Strychnos pseudoquina species were evaluated on in vitro experiments against Leishmania amazonensis. The Strychnos pseudoquina species showed the best biological activity. A bioactivity-guided fractionation was carried out and two flavonoids, quercetin 3-O-methyl ether and strychnobiflavone, were isolated. In vitro assays with Strychnobiflavone flavonoid demosntrated its effectiveness against L. amazonensis and L. infantum, for promastigotes forms and it showed a very low toxicity in murine macrophages and in human erythrocytes. In vivo biodistribution studies done on healthy BALB/c, showed an accumulation of the drug in the animal liver and spleen. The results also indicated the product presence in the mitochondrial level of the species L. infantum, as a possible mechanism of action of flavonoid. Thus, we can conclude that the species S. pseudoquina presents antileishmanial activity and Strychnobiflavone are mainly responsible for such action in the plant; so it could be use in the future to improve the treatment of leishmaniasis.